2013
DOI: 10.1111/jawr.12073
|View full text |Cite
|
Sign up to set email alerts
|

Managing Forests for Increased Regional Water Yield in the Southeastern U.S. Coastal Plain

Abstract: With growing populations fueling increased groundwater abstraction and forecasts of greater water scarcity in the southeastern United States, identifying land management strategies that enhance water availability will be vital to maintaining hydrologic resources and protecting natural systems. Management of forested uplands for lower basal area, currently a priority for habitat improvement on public lands, may also increase water yield through decreased evapotranspiration (ET). To explore this hypothesis, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 44 publications
1
70
2
Order By: Relevance
“…However, chlorophyll-a was a significant predictor of MCY presence. These results are consistent with other recent studies (Rinta-Kanto et al 2009;Lehman et al 2010;Kudela 2011;Otten et al 2012;McLaughlin et al 2013) that have shown a strong positive correlation between MCY and chlorophyll-a for lakes and other freshwater habitats. Our results also demonstrated a cut point of approximately 15 µg L -1 chlorophyll-a, above which cyanobacteria consistently dominated the phytoplankton assemblage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, chlorophyll-a was a significant predictor of MCY presence. These results are consistent with other recent studies (Rinta-Kanto et al 2009;Lehman et al 2010;Kudela 2011;Otten et al 2012;McLaughlin et al 2013) that have shown a strong positive correlation between MCY and chlorophyll-a for lakes and other freshwater habitats. Our results also demonstrated a cut point of approximately 15 µg L -1 chlorophyll-a, above which cyanobacteria consistently dominated the phytoplankton assemblage.…”
Section: Discussionsupporting
confidence: 93%
“…The high concentrations of MCY at these sites suggest serious health implications for both wildlife and humans since there are multiple routes of recreational exposure (Lé vesque et al 2004;Backer et al 2008;Backer et al 2010). The ubiquity of cyanobacteria is of concern in these coastal water bodies, which provide critical habitat for resident and migratory birds and fish, and are often sites of human recreational activities in this urbanized landscape (McLaughlin et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to calculate the increase of water yield we determined the difference in water yield between a forest management under changing climatic conditions (W cc ) and a forest management under current climatic conditions (W nc )-variation in water yield (in kL). Following McLaughlin et al [23] and Susaeta et al [25], we modelled, respectively, water yield W for each forest management under each climatic regime, and the valuation function of increased water yield G(s):…”
Section: Economic Model Specificationmentioning
confidence: 99%
“…Forest thinnings reduce leaf area and forest transpiration, thus the evapotranspiration is reduced and the water yield is increased [21]. Reported increased water yields after removal of basal area through thinnings range between 3%-64% depending on the forest species, age of the forest, location, and intensity of the thinnings [21,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of precipitation that returns to the atmosphere via evapotranspiration can exceed 90% in Florida's highly productive commercial forests (Gholz and Clark 2002), suggesting that Florida's forests, and indeed forests worldwide, are important regulators of stream flow (Jackson et al 2005). The links between forest management and landscape hydrology (e.g., streamflow and aquifer recharge) also illustrate opportunities to mitigate climate change impacts, and possibly regional water supply conflict, by connecting landowners willing to manage their plantation forests at lower density with groups willing to pay for enhanced water yield (McLaughlin et al 2013).…”
Section: Water Resources Under Future Climatementioning
confidence: 99%